Horizontal head titubation in infants with Joubert syndrome: a new finding. (10th May 2014) - Poretti, Andrea; Christen, Hans‐Jürgen; Elton, Lindsay E; Baumgartner, Manuela; Korenke, Georg Christoph; Sukhudyan, Biayna; Hethey, Sven; Cross, Elizabeth; Steinlin, Maja; Boltshauser, Eugen
<x xml:space="preserve">Abstract</x> Aim Head thrusts are well documented in Joubert syndrome and ocular motor apraxia. We provide a detailed clinical characterization of head titubation in 13 young children with Joubert syndrome. Method Detailed characterization of head titubation was assessed by targeted clinical evaluation and/or analysis of videos. Results In 12 of 13 children (eight males, five females; median age 6y, range 2mo–15y) head titubation was first recognized in the first 2 months of age and decreased in severity until spontaneous resolution. In all children, the head titubation was horizontal, high frequency (~3Hz), had small amplitude (5–10°), was never present during sleep, and did not interfere with the neurodevelopment during infancy. In the majority of children, emotion, anxiety, and tiredness were worsening factors for head titubation. Interpretation Head titubation is a benign, early presentation of Joubert syndrome. Head titubation in hypotonic infants should prompt a careful search for Joubert syndrome. Awareness of its occurrence in Joubert syndrome may avoid unnecessary investigations.